Socio-Educational Attitudes and Conceptions About the Youngs With Intellectual Functional Disability in the Andalusian School Context - Negri-Cortés, María Isabel (2021)
Introduction. Personal relationships of young people with intellectual functional diversity (IFD) in their different school contexts and personal life are essential for their full inclusion. Objective. Analyze the social and educational conceptions and attitudes existing, nowadays, in relation to students with IFD. Methodology. We used a mixed research design, for which we had an incidental sample of 38 teachers from six secondary education schools and 37 professionals from nine social entities of Málaga. The data were collected by two ad-hoc questionnaires and 18 interviews to formal and non-formal educational agents. Results. The main results show the difficulties of the educational system to attend to diversity. The attention of these students is delegated to professionals supporting the integration. The interpersonal relationships of these young people are usually with other peers with special educational needs (SEN) and are either very limited or based on mockery and bullying. Paternal behavior of the teachers hinders their autonomy and, as a result, we saw that these young have low self-esteem. Discussion. we propose to improve the self-determination of these young people by raising awareness within the educational community for better conceptions about diversity.